2021
DOI: 10.1016/j.biocon.2021.109076
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related travel restrictions prevented numerous wildlife deaths on roads: A comparative analysis of results from 11 countries

Abstract: Millions of wild animals are killed annually on roads worldwide. During spring 2020, the volume of road traffic was reduced globally as a consequence of the COVID-19 pandemic. We gathered data on wildlife-vehicle collisions (WVC) from Czechia, Estonia, Finland, Hungary, Israel, Norway, Slovenia, Spain, Sweden, and for Scotland and England within the United Kingdom. In all studied countries WVC statistics tend to be dominated by large mammals (various deer species and wild boar), while information on smaller ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…There have been a growing number of AVC cases worldwide due to expanded road networks and growing traffic volumes 19 , which are more intensified in urban environments 20 , 21 . Annually, an estimated 194 million birds and 29 million mammals are killed annually on European roads alone 22 with ungulates alone exceeding 1 million per year 23 . In a recent study, Bíl 22 found that wildlife vehicle collisions (WVC) had mostly reduced in many countries during the COVID-19 lockdown, albeit with varying rates.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a growing number of AVC cases worldwide due to expanded road networks and growing traffic volumes 19 , which are more intensified in urban environments 20 , 21 . Annually, an estimated 194 million birds and 29 million mammals are killed annually on European roads alone 22 with ungulates alone exceeding 1 million per year 23 . In a recent study, Bíl 22 found that wildlife vehicle collisions (WVC) had mostly reduced in many countries during the COVID-19 lockdown, albeit with varying rates.…”
Section: Introductionmentioning
confidence: 99%
“… Łopucki et al (2021) observed a decrease in road-killed hedgehogs by 50% in comparison to previous 2 years of monitoring in the city of Chelm (Poland) during lockdown. Furthermore, a recent study showed a decline in roadkill numbers from 11, mostly European, countries ( Bíl et al, 2021 ), not including Austria. However, after the lockdown the numbers rose again to the previous level.…”
Section: Introductionmentioning
confidence: 99%
“…, police reports, professional monitoring, carcass removal), but not on citizen science data. One study even excluded data based on citizen science from analyses due to potential confounding effects during lockdown periods ( Bíl et al, 2021 ). It is therefore crucial to understand what kind of effects lockdowns have on citizen science data to address potential biases or confounding effects.…”
Section: Introductionmentioning
confidence: 99%
“…the roadkill). For example, Bíl et al [19] found that reduced traffic across 10 European countries and Israel, during spring 2020, decreased the overall road mortality by 19% in comparison with predictions based on 2015-2019 roadkills. Similar results were found by Shilling et al [20] for 4 states in the United States, and by other studies at the local scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that susceptibility to collisions with vehicles partially depends upon individual traits critical for the adaptation to urban environments and man-made infrastructures, like boldness [24] , WVC can exert long-term evolutionary pressures on wildlife populations in anthropized environments [25] . Due to these two aspects and altogether with preliminary evidences on the strong effect of COVID-19 countermeasures on roadkills [19][20][21] [22] , determining robust estimates about shifts in WVC during lockdown periods (LP) across multiple assembly of wildlife species is becoming paramount for obtaining a comprehensive picture about COVID-19 (but also traffic and changes in its volume) as a global driver of ecological change.…”
Section: Introductionmentioning
confidence: 99%